Integration of Islamic Ecological Ethics in Plastic Waste-Based Arts and Culture Learning for Student Creativity - Putri, Nadia; Kusumawati, Yayuk; Hermansyah (Multicultural Islamic Education Review, 2026)
This study aims to analyze the integration of Islamic Ecological Ethics in the utilization of plastic waste in Arts and Culture learning to enhance student creativity at MIS Al-Falah Nipa. The research is motivated by the increasing problem of plastic waste and the suboptimal utilization of the environment as a contextual and meaningful learning resource for Arts and Culture learning. Furthermore, student creativity in learning still tends to be low because students prefer to imitate examples given by teachers rather than develop ideas independently. This study used a qualitative descriptive exploratory research method. The participants consisted of 32 fifth-grade students and one Arts and Culture teacher selected using purposive sampling techniques. Data collection was conducted through observation, semi-structured interviews, and documentation. Data analysis used the Constant Comparative Procedure (CCP) through a continuous process of data reduction, coding, categorization, and drawing conclusions. The results showed that the integration of Islamic Ecological Ethics in Arts and Culture learning based on the utilization of plastic waste was able to increase students' creativity in the aspects of fluency, flexibility, originality, and elaboration. Learning also increased students' ecological awareness through environmentally conscious behavior, responsibility in utilizing plastic waste, and an understanding of the importance of protecting the environment from an Islamic perspective. In addition, project-based learning created a more active, collaborative, and contextual learning atmosphere. Despite constraints such as limited time and facilities, this learning still showed great potential in supporting sustainable education based on Islamic values. This study confirms that the integration of Islamic Ecological Ethics in Arts and Culture learning can be an innovative strategy in forming a creative and environmentally conscious generation starting from elementary school